Assessment of a Chemotherapy Response Score (CRS) System for Tubo-Ovarian High-Grade Serous Carcinoma (HGSC). (May 2019) - Ditzel, Helena M.; Strickland, Kyle C.; Meserve, Emily E.; Stover, Elizabeth; Konstantinopoulos, Panagiotis A.; Matulonis, Ursula A.; Muto, Michael G.; Liu, Joyce F.; Feltmate, Colleen; Horowitz, Neil; Berkowitz, Ross S.; Gupta, Mamta; et al.
Abstract : A chemotherapy response score (CRS) system was recently described to assess the histopathologic response and prognosis of patients with tubo-ovarian high-grade serous carcinoma (HGSC) receiving neoadjuvant chemotherapy. The current study was performed as an independent assessment of this CRS system. We retrospectively identified advanced stage HGSC patients who received neoadjuvant chemotherapy and underwent interval debulking. If available, a hemotoxylin and eosin slide from the omentum and the adnexa was selected for the study. Slides were independently scored by 13 pathologists using the 3-tiered CRS system. Reviewers then received web-based training and rescored the slides. Overall survival and progression-free survival were estimated using the Kaplan-Meier method and compared using the log-rank test. A total of 68 patients with omental (n=65) and/or adnexal (n=59) slides were included in the study. Interobserver reproducibility was moderate for omentum (κ, 0.48) and poor for adnexa (κ, 0.40), which improved for omentum (κ, 0.62) but not for adnexa (κ, 0.38) after online training. For omental slides, a consensus CRS of 1/2 was associated with a shorter median progression-free survival (10.9 mo; 95% confidence interval, 9–14) than a CRS of 3 (18.9 mo; 95% CI, 18–24; P =0.020). In summary, a 3-tiered CRS system of hemotoxylin and eosin–stained omental deposits can yield prognostic information for HGSC patients receiving neoadjuvant chemotherapy, and web-based training improved reproducibility but did not alter determination of clinical outcomes. The CRS system may allow oncologists to identify potential nonresponders and triage HGSC patients for heightened observation and/or clinical trials.